Návrh výběru druhu topných desek dle technologických a ekonomických aspektů - Juřenová, Jana (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2008)
Popis a struktura firmy. Popis a charakteristika druhu topných desek a topných médií. Rozbor současného výběru druhu topných desek. Technické a ekonomické aspekty. Celkové zhodnocení aspektů a návrh nejlepší vhodné varianty.

Description and structure of the company. Description and characteristic of type of heating plates and heating medium. Analysis of the current selection of heating plates. Technological and economics aspects. Total estimation of aspects and suggestion of the best suitable alternate.
Suggestion of Type Selection of heating Plates According to Selected Aspacts
Keywords: Svařovaná topná deska; vrtaná topná deska; topné médium; kalkulace; náklady; technické a ekonomické aspekty.; Welded heating plate; drilled heating plate; heating medium; calculation; burden; technological and economics aspects.